2016
DOI: 10.1089/jcr.2016.0006
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Validity of Caffeine Problems and Diagnostic Criteria for Substance Use Disorders

Abstract: Background: The DSM-5 proposes caffeine use disorder (CUD) as a condition for further study. The objective of this study was to report on the prevalence of CUD and rates of endorsement for each substance use disorder (SUD) criterion in relation to caffeine compared to alcohol and marijuana in a sample of adolescents presenting for medical care in the primary, adolescent, and substance use clinics at an academic medical center. Methods: A convenience sample of patients (N = 213; 66.7% female) aged 12-17 present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…13 Studies have examined the prevalence of substance use disorder criteria as applied to caffeine, but the majority were conducted among special populations such as heavy or treatment-seeking caffeine consumers or psychiatric patients, they preceded the proposed DSM-5 criteria, or had relatively small sample sizes. 6,[16][17][18][19][20][21][22][23][24][25][26][27] The only general population examination of DSM-defined caffeine use disorder in the United States surveyed 162 current caffeine consumers in Vermont and found that 30% of caffeine consumers met generic DSM-IV criteria for substance dependence as applied to caffeine. 6 The estimated prevalence was less than 10% when a key-criteria strategy similar to that proposed by DSM-5 was adopted.…”
Section: Introductionmentioning
confidence: 99%
“…13 Studies have examined the prevalence of substance use disorder criteria as applied to caffeine, but the majority were conducted among special populations such as heavy or treatment-seeking caffeine consumers or psychiatric patients, they preceded the proposed DSM-5 criteria, or had relatively small sample sizes. 6,[16][17][18][19][20][21][22][23][24][25][26][27] The only general population examination of DSM-defined caffeine use disorder in the United States surveyed 162 current caffeine consumers in Vermont and found that 30% of caffeine consumers met generic DSM-IV criteria for substance dependence as applied to caffeine. 6 The estimated prevalence was less than 10% when a key-criteria strategy similar to that proposed by DSM-5 was adopted.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals who regularly consume caffeinated beverages may develop a physical, emotional, and psychological dependence on them and may experience withdrawal symptoms with abrupt discontinuation 3 . According to multiple studies, caffeine use disorder (CUD) is clinically relevant and is included in the 5th edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM‐V) 4,5 …”
Section: Introductionmentioning
confidence: 99%
“…3 According to multiple studies, caffeine use disorder (CUD) is clinically relevant and is included in the 5th edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-V). 4,5 In 2015 the European Food Safety Authority 6 suggested that caffeine intake of 200 mg/day or 3 mg/kg body weight per day is safe for adults; however, daily caffeine intake relative to body weight remains more precise than the absolute amount of daily caffeine. On the other hand, CUD is another crucial factor worth considering, as the daily amount required for dependence varies from person to person.…”
Section: Introductionmentioning
confidence: 99%
“…Az LCA-elemzéshez első körben a kávé-, tea koffeinfogyasztási motivációkra irányuló vizsgálatok nem vizsgálták (Irons et al, 2014), vagy csak részlegesen vizsgálták (Graham, 1988), hogy az egyes koffeintartalmú termékek fogyasztói között felfedezhetők-e különbségek a fogyasztási motivációk terén. A koffeinhasználati zavarra irányuló tanulmányok jelentős része (Harstad et al, 2016;McGregor & Batis, 2016;Striley et al, 2011) (Rogers et al, 1995).…”
Section: Eredményekunclassified